The Concept of Ideology in Marxist Literary Criticism - Hamadi, Lutfi (European Scientific Journal, ESJ, 2017)
This paper attempts an exploration of the development of the Marxist literary theory in general and the concept of ideology in particular. Showing the significant role this theory plays in the field of literary criticism, the paper focuses on remarkable Marxist figures, explores their most notable works, and sheds light on their contributions to the theory and the field of literary criticism. For this purpose, the paper starts with basic Marxist principles of reading literature set by Marx and Engels and examines the changes that occurred with other critics, mainly Althusser, Jameson, and Eagleton in their attempts to show the importance of ideology in explaining literature and understanding its backgrounds, goals, and methods. Thus, the methodology will include an historical overview, shedding light on early Marxist perspectives, comparing and contrasting the contributions and adjustments added by remarkable Marxist thinkers, and illustrating by examples of literary texts and how they are seen and analyzed by these Marxist scholars.